2020
DOI: 10.1186/s12917-020-2255-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute tea tree oil intoxication in a pet cockatiel (Nymphicus hollandicus): a case report

Abstract: Background: Phytotherapy is becoming a more and more common practice, not only for personal care but also for pet care. Nevertheless, we often have to deal with substances on which, in most cases, very little literature is available, even more so if the species of interest are the exotic ones. In particular, the essential oil from the Melaleuca leaves, because of its antinflammatory and antibacterial properties, is widely used and very little is known about its potential toxicity on pet birds. The present pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Animal studies regarding tea tree oil toxicity support this statement, as central nervous system depression, paresis, weakness, ataxia, lethargy and muscle tremors were observed in rats, dogs and cats after dermal application, which probably led to cutaneous absorption (Khan et al, 2014; Vetere et al, 2020; Villar et al, 1994). In rats, additional adverse effects such as obtundation, bloodied noses and weeping were observed (Vetere et al, 2020). It is also reported that the oral administration of tea tree oil might have the potential to lead to pneumonitis and lung injury in humans (Morris et al, 2003).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Animal studies regarding tea tree oil toxicity support this statement, as central nervous system depression, paresis, weakness, ataxia, lethargy and muscle tremors were observed in rats, dogs and cats after dermal application, which probably led to cutaneous absorption (Khan et al, 2014; Vetere et al, 2020; Villar et al, 1994). In rats, additional adverse effects such as obtundation, bloodied noses and weeping were observed (Vetere et al, 2020). It is also reported that the oral administration of tea tree oil might have the potential to lead to pneumonitis and lung injury in humans (Morris et al, 2003).…”
Section: Resultsmentioning
confidence: 96%
“…These reports suggest that the intake of a modest amount of tea tree oil can already lead to ataxia and central nervous system depression, caused by the hydrocarbon components (Bischoff & Guale, 1998;Morris et al, 2003). Animal studies regarding tea tree oil toxicity support this statement, as central nervous system depression, paresis, weakness, ataxia, lethargy and muscle tremors were observed in rats, dogs and cats after dermal application, which probably led to cutaneous absorption (Khan et al, 2014;Vetere et al, 2020;Villar et al, 1994). In rats, additional adverse effects such as obtundation, bloodied noses and weeping were observed (Vetere et al, 2020).…”
Section: Literature Review On Safety and Adverse Effects Of Tea Tree Oilmentioning
confidence: 97%
“…Critically ill birds must be assessed accurately and provided with immediate supportive care [ 69 ]. Specific protection and control plans to reduce anthropogenic causes of admissions, such as gunshots, use of pesticides and other toxic substances (with a direct effect on birds of prey, or indirect, i.e., on prey), and the use of rat glue, can and should be intensified in order to reduce these events to nil.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about predisposing factors involved in avian sensitivity to toxic agents, however several products that are relatively harmless to humans may have profound effects on birds. The most common substances reported to cause toxicosis are ingested heavy metals, such as lead and zinc; inhalant toxins, for instance smoke from cooking or burning material and fumes from aerosols or cleaning agents; pesticides, toxic plants and foods (Bauck & Labounde, 1997;Guthrie et al, 2020;Vetere et al, 2020).…”
Section: Discussionmentioning
confidence: 99%